Comparison of diagnostic accuracy of bactec culture, gene-xpert and histopathology in the diagnosis of genital tuberculosis in women with infertility - Chaudhary, Rachna; Dhama, Vandana; Singh, Manisha; Singh, Shakun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Female genital tuberculosis (FGTB) is often a silent disease sparing no age group but majority of patients are in the reproductive age. In infertility patient’s incidence of FGTB varies from 3-16% in India but the actual incidence of genital tuberculosis may be under reported due to asymptomatic presentation and paucity of investigations. Methods: Prospective case control study was conducted from June 2018 to May 2019 in LLRM Medical College Meerut. A total 100 Endometrial samples were collected during diagnostic laparoscopy from all suspected case of genital TB, presented with either primary or secondary infertility and samples sent for histopathology, Gene-xpert and Bactec culture. Results: Out of 100 samples Bactec culture was positive in 2 samples, Gene-xpert positive in 3 samples. On histopathology out of 100 cases, non-specific endometritis was found in 1 case, tubercular-endometritis in 1 case, proliferative enometrium (anovulatory) in 40 cases and secretory endometrium found in 58 cases. Conclusions: Female genital TB poses a diagnostic dilemma because of its varied presentation and lack of sensitive and specific method of diagnosis. Culture though remains the gold standard of diagnosis of female genital TB, gene-xpert, histopathology, Bactec culture or laparoscopy can be used for starting treatment. Endometrial biopsy on histopathology shows not only Tubercular endometritis but also gives hormone response on endometrium, local factors of endometrium concerning non-specific and specific infections and anovulatory cycles.